Influência do uso de pó de rocha basáltica e biocarvão em latosolo vermelho distroférrico e no cultivo orgânico de phaseolus vulgaris antecedido por plantas solubilizadoras - Grosselli, Mailis Aparecida (2021)
Agriculture has undergone constant transformation processes throughout history that have allowed great advances in soil management in agroecosystems. The latest changes are mainly related to the decrease in the impact of the use of natural resources in agriculture and the improvement in the efficiency of use of available resources. In this perspective, the objective of the present work was to evaluate the performance of basaltic rock dust and biochar in the fertility of weathered soil in an organic cultivation system of Phaseolus vulgaris. Two experiments were carried out simultaneously, in a greenhouse and in the field. In the experiments, a bifactorial arrangement with four doses of rock powder, four doses of biochar and four replications was used. After the implantation of the treatments, a system of succession of cultures was adopted in the following order: Raphanus sativum, Cajanus cajan and Phaseolus vulgaris. The data were subjected to analysis of variance (p <0.05) and subsequent regression analysis or multiple comparison test of Tukey's means (p <0.05), as appropriate. In the greenhouse experiment, there was an interaction between the rock dust and biochar factors, with an increase in the contents of Organic Matter, Organic Carbon, P, K, Ca, Sum of Bases, CTC, K (%), as well as the relationships between Ca/K and Mg/K. There was also a reduction in the aluminum content in the soil due to the interaction between the factors. Rock powder and Biochar in an isolated way positively influenced the contents of Magnesium, Mg (%), Al (%), Saturation by Bases (V%) and reduced the levels of Hydrogen + Aluminum in the soil. Also in the greenhouse experiment, the biochar influenced the length of the aerial part and the total dry mass of the beans. In the field experiment, there was an interaction between the rock dust and biochar factors, significantly increasing the pH (CaCl2), the levels of P, K, Ca, the Sum of Bases, the CTC, and the K (%), in addition to the relationships between Ca/K and Mg/K. The same interaction between the factors reduced the levels of Al, H + Al and Al% in the soil. Rock powder in an isolated way positively influenced the contents of organic matter, organic carbon and the Ca/Mg ratio. In bean plants, the interaction between rock dust and biochar influenced the shoot length. The total dry mass of the bean was influenced by the dose of rock dust and biochar alone, without the interaction between the factors. The set of results allowed to verify the promising use of soil conditioners and remineralizers in the recovery of highly weathered soils, and future works should evaluate their behavior under different edaphoclimatic conditions and agricultural crops.